A Tentative Clinical Study: Colistin Combined with Ceftazidime/Avibactam in the Treatment of Carbapenem-Resistant Gram-Negative Bacilli Infection - Zhang R; Zheng Z; Lu Y; Shi K; Lin Z; Tang S; Shao Z; Yang X; Liu J (Infection and Drug Resistance)
Run Zhang,1,* Zihao Zheng,1,* Yinli Lu,1 Kai Shi,2 Zongbin Lin,1 Siyu Tang,1 Ziqiang Shao,1 Xianghong Yang,1 Jingquan Liu1 1Emergency and Critical Care Center, Intensive Care Unit, Zhejiang Provincial People’s Hospital (Affiliated People’s Hospital), Hangzhou Medical College, Hangzhou, Zhejiang Province, 310014, People’s Republic of China; 2Department of Respiratory Medicine, The Affiliated Hospital of Hangzhou Normal University, Hangzhou, Zhejiang Province, 310015, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingquan Liu, Emergency and Critical Care Center, Intensive Care Unit, Zhejiang Provincial People’s Hospital, Affiliated People’s Hospital, Hangzhou Medical College, Hangzhou, Zhejiang Province, 310014, People’s Republic of China, Email liujqaticu@163.comPurpose: The emergence of carbapenem-resistant Gram-negative bacteria (CR-GNB) has led to a critical challenge in antimicrobial therapy. This study aimed to assess the efficacy of colistin (COL) combined with ceftazidime/avibactam (CAZ/AVI) in the treatment of CR-GNB infections.Patients and Methods: A retrospective, single-center observational study was conducted on patients diagnosed with CR-GNB infections who were treated with COL combined with CAZ/AVI (C/C), COL combined with Tigecycline (C/T), and COL combined with meropenem (C/M). The primary outcome measure was the rate of microbiological clearance within seven days, while secondary outcomes included changes in inflammatory markers, severe illness-related scores, length of stay, and survival rates.Results: Among the 95 patients analyzed, the C/C treatment regimen resulted in a higher rate of microbiological clearance (64.7%) compared to C/T (24.1%) and C/M (25.0%) (P=0.002 and P=0.001). In the subgroup analysis for treating infections caused by carbapenem-resistant Klebsiella pneumoniae (CRKP), the 7-day microbial clearance rates in the C/C, C/T, and C/M groups were 57.9%, 25.0%, and 29.4%, respectively (P = 0.122). Inflammatory markers, including white blood cell count, c-reactive protein, and procalcitonin, showed improvements in three groups. The decrease of some indicators was statistically significant. However, no significant differences in mortality rates were observed across the treatment groups. Furthermore, the survival curve analysis indicates that the survival time of the C/M treatment regimen is significantly longer than that of the C/C treatment regimen.Conclusion: The C/C treatment regimen appears to be more effective in achieving microbiological clearance and improving inflammatory parameters in patients with CR-GNB infections. While the impact on survival rates and survival duration requires further investigation, the C/C regimen warrants consideration as a potent therapeutic option for CR-GNB infections.Keywords: carbapenem-resistant Gram-negative bacteria, colistin, ceftazidime/avibactam, tigecycline, meropenem